Derivatives, the shape of international capital flows and the virtues of prudential regulation - Randall Dodd (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
The paper studies the trend towards the use of securities as a vehicle to transfer capital to developing economies, and how it is linked to the increasing use of derivatives transactions in developing countries. It also provides a descriptive analysis of how each type of capital vehicle is associated with various derivatives instruments. It then looks at how various derivative instruments decompose the risks associated with each capital vehicle, price then separately and then allow those risks to be redistributed. The paper next analyses how this portfolio of capital and derivatives can potentially add to the vulnerability of developing country financial systems to external shocks and domestic policy failures. It concludes with a set of policy recommendations in the form of prudential market regulations that are designed to reduce excessive or unproductive risk taking, reduce the vulnerability of the financial system and mitigate the impact of financial sector disruptions on the overall economy. – derivates ; capital flows ; risk management ; international finance
Keywords: F3; F4; G1; G2; 330; Kapitalmobilität; Portfolio-Investition; Finanzderivat; Entwicklungsländer